OP0017 Lack of placental transfer of certolizumab pegol during pregnancy: results from crib, a prospective, postmarketing, multicenter, pharmacokinetic study. (15th June 2017) - Mariette, X; Flynn, A; Förger, F; Moltό, A; Flipo, R-M; Tubergen, A van; Shaughnessy, L; Simpson, J; Teil, M; Helmer, E; Wang, M; Chakravarty, E
Abstract : Background: There is a need for effective and safe treatment during pregnancy in women affected by chronic active inflammatory diseases, such as rheumatoid arthritis. Adequate disease control is crucial to ensure the best fetal and maternal health, and reduce adverse pregnancy outcomes. 1, 2 Anti-TNFs are an effective therapeutic option, but because most cross the placenta, they are often stopped during pregnancy. 3, 4 Certolizumab pegol (CZP), due to its Fc-free molecular structure, has no active placental transfer compared to other anti-TNFs. 5, 6 Objectives: To accurately measure the potential level of placental transfer of CZP from mothers to infants using a highly sensitive, CZP-specific assay. Methods: CRIB (NCT02019602 ) was a pharmacokinetic (PK) study of pregnant women (≥30 weeks [wks] gestation) receiving commercial CZP (maintenance dose) for an approved indication; last dose was within 35 days prior to delivery. Blood samples were collected from the mothers, umbilical cords, and infants at delivery, and infants again at Wks 4 and 8 post-delivery. CZP concentration was measured with a sensitive, CZP-specific electrochemiluminescence immunoassay validated in plasma (LLOQ=0.032 μg/mL; 10-fold lower than assay used in prior CZP PK studies 6, 7 ). Results: 21 CZP-treated pregnant women were screened; 16 entered the study (Table). Maternal CZP plasma levels at delivery were within the expected therapeutic range (median [range]: 24.4 [5.0–49.4] μg/mL). Of the 16 infants delivered, 2 samples were excluded: 1 due to missing data, 1 due to implausible PK data. 13/14 infants had no quantifiable CZP levels at birth (<0.032 μg/mL); 1 infant had a minimal CZP level of 0.042 μg/mL (infant/mother plasma ratio: 0.09%); no infants had quantifiable levels at Wks 4 and 8 (Figure). 3/15 umbilical cord samples had quantifiable CZP levels (maximum: 0.048 μg/mL); 1 umbilical cord collapsed and was excluded. No anti-CZP antibodies were detected in mothers, umbilical cords, or infants. The infants of CZP-exposed mothers had a safety profile consistent with that of unexposed similar-age infants. Conclusions: Using a highly sensitive assay, CZP levels were below LLOQ in 13/14 infant blood samples at birth, and all samples at Wks 4 and 8. This indicates no to negligible placental transfer of CZP from mothers to infants, suggesting lack of in utero fetus exposure during the second and third trimesters. These results support continuation of CZP treatment during pregnancy. References: de Man Y. Arthritis Rheum 2009;60:3196–206. Morales M. Hepatogastroenterology 2000;47:1595–8. Ng S. Expert Rev Clin Immunol 2013;9:161–73. Østensen M. Curr Opin Pharmacol 2013;13:470–5. Porter C. J Reprod Immunol 2016;116:7–12. Mahadevan U. Clin Gastroenterol Hepatol 2013;11:286–92. Lacroix B. Gastroenterol 2010;138:S163–4. Acknowledgements: This study was funded by UCB Pharma. We are indebted to the mothers and their infants for their altruistic participation. Editorial services were provided by Costello Medical Consulting. Disclosure of Interest: X. Mariette Grant/research support from: Biogen, Pfizer, UCB Pharma, Consultant for: Bristol-Myers Squibb, GlaxoSmithKline, LFB, Pfizer, UCB Pharma, A. Flynn Grant/research support from: UCB Pharma, F. Förger Grant/research support from: UCB Pharma, Speakers bureau: Mepha, Roche, UCB Pharma, A. Moltό Grant/research support from: MSD, AbbVie, Pfizer, UCB Pharma, Consultant for: MSD, AbbVie, Pfizer, UCB Pharma, R.-M. Flipo Consultant for: UCB Pharma, A. van Tubergen Grant/research support from: Pfizer, AbbVie, UCB Pharma, Janssen-Cilag, Celgene, Novartis, MSD, Consultant for: AbbVie, Novartis, Janssen-Cilag, Pfizer, Speakers bureau: MSD, Janssen-Cilag, Pfizer, L. Shaughnessy Employee of: UCB Pharma, J. Simpson Employee of: UCB Pharma, M. Teil Employee of: UCB Pharma, E. Helmer Employee of: UCB Pharma, M. Wang Employee of: UCB Pharma, E. Chakravarty Grant/research support from: UCB Pharma